PERAN MAHASISWA DALAM MEMBERIKAN PEMAHAMAN KEPADA MASYARAKAT TERKAIT COVID – 19 AGAR TETAP PRODUKTIF DI MASA PANDEMI - Arif Budi Sulistyo (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
KKM (Kuliah Kerja Mahasiswa) is a forum for college students to apply their knowledge gained at universities and play an active role in potential development by providing knowledge of Covid-19 to the community to encourage them remain productive during the pandemic. The main purpose of dedication is to fulfill one aspect of Tri Dharma University, namely dedication of college student to community and making village communities become independent. The method used is observation of the social condition’s community, socialization of the work program, then counselling and assistance to the village community. The result of dedication is through empowerment to make villages stronger and independent, such as in the field of education, by teaching elementary school students to read, count and provide knowledge about Covid-19, then in the health sector, by providing counselling about the impact of covid virus, also distributed masks and hand sanitizer to residents, then in the field of hygiene is by making trash cans to be placed at several points